Interrupted PET coupled TBET process for the design of a specific receptor for Hg2+ and its intracellular detection in MCF7 cells - Saha, Sukdeb; Mahato, Prasenjit; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Chemical Communications, 2012)
A new coumarin–rhodamine conjugate constitutes a unique example of the interrupted PET coupled TBET response for developing an imaging reagent for determining the intracellular distribution of Hg2+ in MCF7 cells exposed to [Hg2+] as low as 2 ppb.

New chemodosimetric reagents as ratiometric probes for cysteine and homocysteine and possible detection in living cells and in blood plasma - Das, Priyadip; Mandal, Amal Kumar; Chandar, Nellore Bhanu; Baidya, Mithu; Bhatt, Harshad B.; Ganguly, Bishwajit; Ghosh, Sudip K.; Das, Amitava (Chemistry a European Journal, 2012)
In this work, we have rationally designed and synthesized two new reagents (L1 and L2), each bearing a pendant aldehyde functionality. This aldehyde group can take part in cyclization reactions with β- or γ-amino thiols to yield the corresponding thiazolidine and thiazinane derivatives, respectively. The intramolecular charge-transfer (ICT) bands of these thiazolidine and thiazinane derivatives are distinctly different from those of the molecular probes (L1 and L2). Such changes could serve as a potential platform for using L1 and L2 as new colorimetric/fluorogenic as well as ratiometric sensors for cysteine (Cys) and homocysteine (Hcy) under physiological conditions. Both reagents proved to be specific towards Cys and Hcy even in the presence of various amino acids, glucose, and DNA. Importantly, these two chemodosimetric reagents could be used for the quantitative detection of Cys present in blood plasma by using a pre-column HPLC technique. Such examples are not common in contemporary literature. MTT assay studies have revealed that these probes have low cytotoxicity. Confocal laser scanning micrographs of cells demonstrated that these probes could penetrate cell membranes and could be used to detect intracellular Cys/Hcy present within living cells. Thus, the results presented in this article not only demonstrate the efficiency and specificity of two ratiometric chemodosimeter molecules for the quantitative detection of Cys and Hcy, but also provide a strategy for developing reagents for analysis of these vital amino acids in biological samples.
Keywords: charge transfer; chemodosimetric detection; cysteine/ homocysteine sensors; fluorescent probes; imaging agents; ratiometric probes

Recognition of Hg 2+ and Cr 3+ in physiological conditions by a rhodamine derivative and its application as a reagent for cell-imaging studies - Saha, Sukdeb; Mahato, Prasenjit; Reddy, Upendar G.; Suresh, E.; Chakrabarty, Arindam; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Inorganic Chemistry, 2012)
A new rhodamine-based receptor, derivatized with an additional fluorophore (quinoline), was synthesized for selective recognition of Hg2+ and Cr3+ in an acetonitrile/HEPES buffer medium of pH 7.3. This reagent could be used as a dual probe and allowed detection of these two ions by monitoring changes in absorption and the fluorescence spectral pattern. In both instances, the extent of the changes was significant enough to allow visual detection. More importantly, the receptor molecule could be used as an imaging reagent for detection of Hg2+ and Cr3+ uptake in live human cancer cells (MCF7) using laser confocal microscopic studies. Unlike Hg(ClO4)2 or Hg(NO3)2 salts, HgCl2 or HgI2 failed to induce any visually detectable change in color or fluorescence upon interaction with L1 under identical experimental conditions. Presumably, the higher covalent nature of HgII in HgCl2 or HgI2 accounts for its lower acidity and its inability to open up the spirolactam ring of the reagent L1. The issue has been addressed on the basis of the single-crystal X-ray structures of L1·HgX2 (X– = Cl– or I–) and results from other spectral studies.

Recognition of Hg2+ion through restricted imine isomerization: crystallographic evidence and imaging in live cells - Mandal, Amal Kumar; Suresh, Moorthy; Das, Priyadip; Suresh, E.; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Organic Letters, 2012)
A newly synthesized imine-based receptor (L) showed remarkable specificity toward the Hg2+ ion in aqueous media over other metal ions. Coordination of L to Hg2+ induces a turn-on fluorescence response. This was explained based on the restricted imine isomerization along with PET on coordination to Hg2+. X-ray structural evidence tends to favor a C–C bond rotation rather than C═N isomerization for adopting a favorable conformation in L for coordination to Hg2+. This reagent could be used for imaging the accumulation of Hg2+ ions in HeLa cells.

CN? specific turn-on phosphorescent probe with probable application for enzymatic assay and as an imaging reagent - Reddy, Upendar G.; Das, Priyadip; Saha, Sukdeb; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Chemical Communications, 2013)
A new “turn-on” luminescence probe for imaging the uptake of 0.2 ppm inorganic CN− in live HeLa cells as well as for probing the CN− generation through an enzymatic process in a virtual aqueous medium at appropriate pH.

Designing a thiol specific fluorescent probe for possible use as a reagent for intracellular detection and estimation in blood serum: kinetic analysis to probe the role of intramolecular hydrogen bonding - Das, Priyadip; Mandal, Amal Kumar; Reddy, Upendar G.; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Organic & Biomolecular Chemistry, 2013)
A new and simple chemodosimetric probe L-1 is utilized for the selective detection of biothiols in the presence of other relevant amino acids under physiological conditions (pH = 7.4). This eventually led to a turn-off luminescence response due to an effective photoinduced electron transfer based signaling mechanism. A comparison of the results of the fluorescence kinetic analysis and H-1 NMR studies of the reaction between thiol and L-1 or the analogous compound L-2 revealed the role of intramolecular hydrogen bonding in activating the imine functionality towards nucleophilic addition. Such an example is not common in contemporary literature. Conventional MTT assay studies revealed that this probe (L-1) has low cytotoxicity. Results of the cell imaging studies revealed that this probe was cell membrane permeable and could detect the intracellular distribution of biothiols within living HeLa cells. Furthermore, our studies with human blood plasma demonstrated the possibility of using this reagent for the quantitative optical detection of total biothiols in biological fluid. Such an example for the detection of biothiols in real biological samples is rare in the contemporary literature. These results clearly demonstrate the possibility of using this reagent in medicinal biology and diagnostic applications.

New chemodosimetric probe for the specific detection of Hg2+ in physiological condition and its utilisation for cell imaging studies - Saha, Sukdeb; Agarwalla, Hridesh; Gupta, Hariom; Baidya, Mithu; Suresh, E.; Ghosh, Sudip K.; Das, Amitava (Dalton Transactions, 2013)
A dithiane derivative of BODIPY is synthesized. This new reagent could be used for the specific and instantaneous detection of Hg2+ in physiological condition. This dithiane reagent reacts specifically with Hg2+ to regenerate the parent BODIPY-aldehyde with consequential change in visually detectable optical responses and this provides the possibility of using this reagent as a colorimetric probe or as a fluorescent biomarker/imaging reagent. Further, non-covalent interactions could be utilized for formation of an inclusion complex with biologically benign beta-cyclodextrin for enhancing its solubility in aqueous environment and this included adduct could be used as a fluorescent marker and imaging reagent for Hg2+. Uptake of Hg2+ ions in live HeLa cells, exposed to a solution having Hg2+ ion concentration as low as 2 ppb, could also be detected by confocal laser microscopic studies.